2008
DOI: 10.1128/jb.00777-08
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient In Vitro Site-Specific Recombination System Based on Streptomyces Phage φBT1 Integrase

Abstract: The Streptomyces phage BT1 encodes a site-specific integrase of the large serine recombinase subfamily. In this report, the enzymatic activity of the BT1 integrase was characterized in vitro. We showed that this integrase has efficient integration activity with substrate DNAs containing attB and attP sites, independent of DNA supercoiling or cofactors. Both intra-and intermolecular recombinations proceed with rapid kinetics. The recombination is highly specific, and no reactions are observed between pairs of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 19 publications
3
61
0
Order By: Relevance
“…The minimal sizes of substrate DNAs for the serine integrases are similar, but not identical. In general, the minimal sizes of attB sites for the serine integrases are less than 40 bp, but those of attP sites are larger than 40 bp (38 and 48 bp for Bxb1 integrase, Ghosh et al 2003; 36 and 48 bp for BT1 integrase, Zhang et al 2008).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimal sizes of substrate DNAs for the serine integrases are similar, but not identical. In general, the minimal sizes of attB sites for the serine integrases are less than 40 bp, but those of attP sites are larger than 40 bp (38 and 48 bp for Bxb1 integrase, Ghosh et al 2003; 36 and 48 bp for BT1 integrase, Zhang et al 2008).…”
Section: Figmentioning
confidence: 99%
“…The reversibility and substrate speciWcity of TG1 integrase Serine integrases reported so far are known to be irreversible for the integration reaction in the absence of accessory factors (directionality factor) except for BT1 integrase (Zhang et al 2008). Next, we examined whether TG1 integrase can reverse the integration reaction in the absence The recombined product in this reaction is a linear DNA molecule containing attL and attR.…”
Section: Over-production and Puriwcation Of Tg1 Integrasementioning
confidence: 99%
“…1). The mechanism of insertion was studied in vitro where it was shown that the minimal attB and attP sites comprise 36 and 48 bp, respectively [106]. The integration process was very eYcient with attB and attP substrates, but was also measurable with attL and attR sequences, implying that Int might excise BT1 in vivo at some frequency in the absence of other factors.…”
Section: Temperate Bacteriophages That Utilize Large Serine Recombinasesmentioning
confidence: 99%
“…Briefly, primers 0655U-F/0655U-R and 0655D-F/0655D-R were separately used to amplify the upstream and downstream homologous arms of rifZ, and the PCR fragments were introduced into the XcmI site of pFDZ101 and pFDZ103 to obtain pDZL101 and pDZL103 (Table 2), respectively. pDZL101, pDZL103, and pTA0613 were linearized and tandemly assembled with pFDZ100 using BT1 integrase (38) to produce the knockout plasmid pDZL104, which was further electroporated into U32 to knock out rifZ. Mutants were selected on Bennet plates containing apramycin (50 g/ml) and verified by PCR employing primers 0655CH-UF/ 0655CH-UR and 0655CH-DF/0655CH-DR.…”
Section: Characterization Of the Transposon Insertional Sites In Mutamentioning
confidence: 99%